The Influence of Principal Leadership And Teacher Performance on Students' Academic Achievements In Elementary School Groups Iwest Likupang District, North Minahasa Regency - Suratman, Suratman; Pinontoan, Marien; Manganganti, Jeanne (Abdurrauf Science and Society, 2025)
This study aims to determine the effect of principal leadership and teacher performance on elementary school students' academic achievement. The study was conducted at Elementary School Gugus I, West Likupang District, involving 80 students, 1 principal, and 12 teachers. The method used is a quantitative method with a multiple linear regression approach. Data collection instruments are in the form of questionnaires and documentation. The results of the study indicate that principal leadership has a positive and significant effect on academic achievement, as well as teacher performance which also makes a significant contribution. Simultaneously, both variables have a synergistic effect on student learning outcomes. It is recommended that principals maintain a democratic leadership style and continue to improve teacher professionalism to support improved student academic achievement.